PENDAMPINGAN KOMUNIKASI POLITIK TERHADAP PARTISIPASI MASYARAKAT DALAM PEMILIHAN KADES DI DESA TANJUNG AGUNG SELATAN KECAMATAN LAIS KABUPATEN MUSI BANYUASIN - Sulistijanto, Andi Budi; Saladin, Diany Putri Pratiwi (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2021)
The people in Tanjung Agung Selatan Village, Lais District, Musi Banyuasin Regency, have a low level of education. This is inversely proportional to the level of community participation in the direct election of the Tanjung Agung Selatan Village Head, Lais District, Musi Banyuasin Regency. Voters' participation rate is quite high at 60%, while the level of education is low at 40%. This shows that there is an abnormality between the low level of community education and community participation in choosing village heads. The purpose of this study was to determine how the influence of education level on the election of village heads in Tanjung Agung Selatan Village, Lais District, Musi Banyuasin Regency, the level of community participation in direct village head elections, and the factors that influence the community's encouragement to choose village heads directly. This research is included in the type of qualitative descriptive research. Researchers obtained data through observation, interviews and documentation as well as analyzing the data. Based on the research results, it is known that the high level of community participation in village head elections is due to a sense of kinship and community encouragement as voters, and the level of community education does not affect community participation in village head elections. This is because people who have education are indifferent and do not want to participate in politics. Therefore, the level of community education in Tanjung Agung Selatan Village, Lais District, Musi Banyuasi Regency has no effect on the level of community participation in the election of their village head.